PM2.5 levels strongly associate with multiple sclerosis prevalence in the Province of Padua, Veneto Region, North-East Italy. (November 2019) - Tateo, Fabio; Grassivaro, Francesca; Ermani, Mario; Puthenparampil, Marco; Gallo, Paolo
Background: Incidence and prevalence trends of multiple sclerosis (MS) in the Province of Padua, North-East Italy, suggest that environmental factors may be associated with increased MS risk. Objective: To investigate the association of PM2.5 with MS prevalence in one of the most polluted geographical area of Italy. Methods: In total, 1435 Italian MS patients residing in the Province of Padua were enrolled. The province surface was classified into urban areas, isolated villages, industrialized places, and countryside. Satellite-derived dust-free and sea salt-free PM2.5 concentrations (annual average 1998–2015, μg/m 3 ) allowed the identification of 18 classes of territorial sections with statistically evaluable numbers of inhabitants. Possible correlations between residential locality types, PM2.5 concentrations, and MS prevalence were investigated. Results: MS prevalence was significantly ( p  < 0.0001) higher in urban areas (ranging from 219 in Padua City to 169/100, 000 in other urban areas) compared to isolated villages (116/100, 000) or rural domains (109/100, 000) and strongly correlated with the annual average concentration of PM2.5 ( r  = 0.81, p  < 0.001). Regression analysis further associated MS cases with PM.2.5 average concentration ( β  = 0.11, p  < 0.001). Conclusion: In the Province of Padua, MS prevalence is strongly associated with PM2.5 exposure suggesting that air pollutants may be one of the possible environmental risk factors for MS.